Reconstructing Mubtada’–Khabar Relations in Arabic Nominal Sentences: An Integrative Literature Review and Implications for Nahwu Pedagogy - Nurul Qiftiah; Muhammad Solihin Pranoto; Mafkira Azahra (Tanwiruna: Jurnal Pendidikan dan Sosial Keagamaan, 2026)
This study aims to analyze mubtada'-khabar as a prediction system in the number of ismiyyah and its implications for nahwu learning. This study uses a qualitative approach with an integrative literature study design through the study of the classic nahwu book and cutting-edge scientific articles relevant to Arabic syntax, nahwu learning, and i’rāb analysis. Data were analyzed using conceptual content analysis through unit of meaning identification, category encoding, and interpretive synthesis. The results of the study show that mubtada'-khabar cannot be understood only as two elements of marfū’ in the basic pattern but as syntactic-semantic relations that build meaning, information focus, affirmation, and communicative functions in Arabic texts. Mubtada’ can be present in the form of ma’rifah, conditional nakirah, or the construction of saddu masadda al-khabar, while khabar can be in the form of mufrad, sum, and syibh al-jumlah. In addition, the phenomena of taqdīm–ta’khīr and nawāsikh show that changes in structure and i’rāb are also related to changes in meaning. The implications of this study emphasize the need for nahwu learning grounded in syntactic, contextual, and gradual functions so that students can understand both the structure and the meaning of Arabic texts.